Taxonomic changes in Ichneumonoidea (Hymenoptera), and notes on certain type specimens - Broad, Gavin R. (Zootaxa, 2021)
The following new synonymies are established: Acrodactyla iliensis Sheng & Bian 1996 = Acrodactyla lachryma Pham, Broad, Matsumoto & Böhme 2012, syn. nov.; Euceros Gravenhorst 1829 = Lentocerus Dong & Naito 1999, syn. nov.; Euceros pruinosus (Gravenhorst 1829) = Lentocerus dentatus Dong & Naito 1999, syn. nov.; Euceros sensibus Uchida 1930 = Lentocerus lijiangensis Dong & Naito 1999, syn. nov.; Gyroneuron Kokujev 1901 = Cyclophatnus Cameron 1910, syn. nov.; Gyroneuron flavum (Cameron 1910) = Gyroneuron testaceator Watanabe 1934, syn. nov.; Liotryphon strobilellae (Linnaeus 1758) = Townesia qinghaiensis He 1996, syn. nov. The following are new combinations: Aleiodes insignis (Brues 1926), Aleiodes lateralis (Cameron 1905), Aleiodes maculicornis (Brues 1926), Aleiodes siccitesta (Morley 1937), Cyclophatnus flavum (Cameron 1910), Rhaconotus striatulus (Cameron 1909), Tolonus cingulatorius (Morley 1912), Zatypota tropica (Morley 1912). Netelia morleyi Townes, Townes & Gupta 1961 is transferred from the subgenus Netelia Gray 1860 to the subgenus Paropheltes Cameron 1907. One new replacement name is proposed: Aleiodes philippinensis nom. nov. for Rhogas lateralis Baker 1917, nec Troporhogas lateralis Cameron 1905. Lectotypes are designated for Antrusa persimilis Nixon 1954, Rhyssalus striatulus Cameron 1909, Troporhogas trimaculata Cameron 1905, Hemiteles cingulatorius Morley 1912, Paniscus ferrugineus Cameron 1889 and for Xanthojoppa inermis Morley 1917. Some previously overlooked type specimens are interpreted and illustrated and some errors in the literature corrected. Hosts are recorded for two genera of Ichneumoninae for the first time: Catadelphops nasutus (Heinrich 1962) was reared from Proserpinus terlooii (Edwards 1875) (Lepidoptera: Sphingidae) in the USA, and Aethianoplis excavata (Roman 1910) was reared from Precis octavia (Cramer 1777) (Lepidoptera: Nymphalidae) in Uganda.